A neural crest cell isotropic-to-nematic phase transition in the developing mammalian gut - Nicolas R. Chevalier; Yanis Ammouche; Anthony Gomis; Lucas Langlois; Thomas Guilbert; Pierre Bourdoncle; Sylvie Dufour (Communications Biology, 2021)
Chevalier et al. report that enteric neural crest cells transit during fetal development from an isotropic cell network to a square grid concomitantly with circular smooth muscle differentiation. They propose that smoothmuscle associated extracellular matrix drives this reorientation transition.